The Correlation of Perception with Men's Participation in Family Planning at Sinoa Bantaeng Public Health Center - Qudratullah Qudratullah; Nurul Fitrianti (Proceeding International Conference Of Innovation Science, Technology, Education, Children And Health, 2023)
Male participation in family planning is still low. Based on the 2015 health demographic survey, the number of male family planning acceptors was only 6.5% and only 2.3% in Bantaeng. The low participation of husbands in the practice of using male contraception is basically inseparable from the assumptions or perceptions that tend to still hand over family planning responsibilities to women. The purpose of this study was to determine the relationship between men's perceptions and participation in family planning in the working area of Sinoa Health Center, Bantaeng. This type of research is a descriptive study using a cross sectional family planning participants with a sampling technique that was purposive sampling. Data analysis used univariate and bivariate analysis by chi square. The results of the chi-square test showed that perception (p value 0.14)) <α (0.05) was related to participation in family planning. This study shows that there is a relationship between men's perceptions and participation in family planning in the working area of the Sinoa Bantaeng Health Center. The challenges with the participation of men in family planning such as family planning are prohibited by religion, family planning is the responsibility of wives and men more valuable than women. So that midwives can provide counseling to Fertile Age Couples (FAC) for family planning programs by inviting men or husbands in male contraception and as additional information for male contraception services.